Quorum Quenching Lactonase Strengthens Bacteriophage and Antibiotic Arsenal Against Pseudomonas aeruginosa Clinical Isolates - Mion, Sonia; Rémy, Benjamin; Plener, Laure; Brégeon, Fabienne; Chabrière, Eric; Daudé, David (Frontiers in Microbiology, 2019)
Many bacteria use quorum sensing (QS), a bacterial communication system based on the diffusion and perception of small signaling molecules, to synchronize their behavior in a cell-density dependent manner. QS regulates the expression of many genes associated with virulence factor production and biofilm formation. This latter is known to be involved in antibiotic and phage resistance mechanisms. Therefore, disrupting QS, a strategy known as quorum quenching (QQ), appears to be an interesting way to reduce bacterial virulence and increase antibiotic and phage treatment efficiency. In this study, the ability of the QQ enzyme SsoPox-W263I, a lactonase able to degrade acyl-homoserine lactones, was investigated for quenching both virulence and biofilm formation in clinical isolates of Pseudomonas aeruginosa from diabetic foot ulcers, as well as in the PA14 model strain. These strains were further evolved to resist to bacteriophage cocktails. Overall, 10 antibiotics or bacteriophage resistant strains were evaluated and SsoPox-W263I was shown to decrease pyocyanin, protease and elastase production in all strains. Furthermore, a reduction of more than 70% of biofilm formation was achieved in six out of ten strains. This anti-virulence potential was confirmed in vivo using an amoeba infection model, showing enhanced susceptibility towards amoeba of nine out of ten P. aeruginosa isolates upon QQ. This amoeba model was further used to demonstrate the ability of SsoPox-W263I to enhance the susceptibility of sensitive and phage resistant bacteria to bacteriophage and antibiotic.